Correction: High precision, localized proton gradients and fluxes generated by a microelectrode device induce differential growth behaviors of pollen tubes. Issue 9 (20th April 2017) - Hu, Chengzhi; Vogler, Hannes; Aellen, Marianne; Shamsudhin, Naveen; Jang, Bumjin; Burri, Jan T.; Läubli, Nino; Grossniklaus, Ueli; Pané, Salvador; Nelson, Bradley J.
Abstract : Correction for 'High precision, localized proton gradients and fluxes generated by a microelectrode device induce differential growth behaviors of pollen tubes' by Chengzhi Hu et al., Lab Chip, 2017, 17, 671–680.